Anti-pilling wear-resistant composite fabric and preparation method thereof

By using a layered composite technology of base fabric, hot melt adhesive web and breathable polyester face film, the problems of easy pilling and insufficient abrasion resistance of polyester fiber fabrics are solved, and a composite fabric with high comfort and durability is achieved.

CN120327065BActive Publication Date: 2025-11-07ZHEJIANG CHALET GARMENTS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510615270.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-14
Publication Date
2025-11-07
Estimated Expiration
2045-05-14

AI Technical Summary

Technical Problem

Polyester fiber fabrics are prone to pilling and lack abrasion resistance. Existing technologies struggle to improve anti-pilling performance while maintaining breathability and waterproofness.

Method used

The fabric is made of a base fabric, a hot melt adhesive web and a breathable polyester membrane. The breathable polyester membrane is composed of modified polyester resin, nano-activated alumina, compatibilizer, lubricant, antioxidant and light stabilizer. It is formed into a pilling-resistant and wear-resistant composite fabric through biaxial stretching and hot pressing.

Benefits of technology

It achieves excellent anti-pilling and abrasion resistance of composite fabrics, while maintaining good moisture permeability and waterproofness, thus improving the comfort and durability of the fabric.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120327065B_ABST
    Figure CN120327065B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of anti-pilling wear-resistant composite fabric and its preparation method, belong to the technical field of laminated composite fabric.The composite fabric is formed by the hot-pressing of base cloth, hot melt adhesive screen film and moisture permeable polyester film, the components of moisture permeable polyester film are: 19-27wt% of nano active alumina, 2.5-3.2wt% of compatible agent, 1.4-1.8wt% of lubricant, 0.12-0.15wt% of antioxidant and 0.06-0.07wt% of light stabilizer, and the balance is modified polyester resin;Modified polyester resin is made into intermediate by amine-ester exchange of methyl trifluoroacetate and diallylamine, then made into modified monomer by click addition of double bond introduced in intermediate molecule with mercaptoethanol, and finally copolymerized with ethylene glycol and terephthalic acid by modified monomer;The modified monomer block chain in modified polyester resin interacts with modified polyester resin, effectively solves the multi-performance contradiction of fabric moisture permeability, waterproof, wear resistance and anti-pilling.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of laminated composite fabric, and particularly relates to an anti-pilling wear-resistant composite fabric and a preparation method thereof. BACKGROUND

[0002] Polyester fabric, also known as polyester fabric, has high strength, good weather resistance and good dimensional stability, and is popular in both civilian and industrial use. However, due to the chemical composition and structural characteristics of polyester fiber itself, it is prone to pilling during use, and the pilling makes the fabric lack wear resistance, which is difficult to meet the comfortable and high-end clothing requirements.

[0003] In view of the pilling problem of polyester fabric, the traditional technology adopts low-adhesion chip spinning, profile spinning and other processes to increase the cohesion between fibers, which can optimize the anti-pilling performance to a certain extent, and the anti-pilling grade can reach about 3.5 level, but it is still difficult to meet the requirements of high-grade clothing fabric, and the profile spinning requires improvement of the spinneret and other equipment, which makes the fabric production equipment lack universality; in the prior art, the film material is combined with the polyester base cloth through laminated composite technology, and the fibers are fixed to avoid fiber sliding from the source, effectively solving the problem of fabric pilling, and the change of production line and equipment is small.

[0004] Polyester film, such as PET (polyethylene terephthalate), has high strength, high wear resistance and suitable cost, and is an optimal surface layer material for anti-pilling fabric. However, polyester material has poor air permeability, which is good for industrial fabrics such as tarpaulin and waterproof cloth, but poor for comfortable clothing fabric; in the prior art, ultra-fine fillers are introduced into polyester material as pore-forming agents, and a stretching process is used to obtain a polyester film layer with a certain porosity, which is combined with traditional fabric to obtain good moisture permeability. However, the pore-forming effect of these ultra-fine fillers is generally poor, and the filler separates from the polyester matrix during the stretching process, resulting in deterioration of the mechanical properties of the film layer. A large amount of filler is prone to crack in the film material during the stretching process, resulting in a decrease in the waterproofness of the film layer, and a contradiction between moisture permeability, waterproofness and mechanical properties, which restricts the development of anti-pilling fabric. SUMMARY

[0005] In order to solve the technical problems mentioned in the background art, the purpose of the present application is to provide an anti-pilling wear-resistant composite fabric and a preparation method thereof.

[0006] The purpose of the present application can be achieved by the following technical solutions:

[0007] The application discloses an anti-pilling wear-resistant composite fabric which is formed by hot-pressing a base cloth, a hot-melt adhesive screen and a moisture-permeable polyester film, wherein the moisture-permeable polyester film is composed of 19-27wt% of nano active alumina, 2.5-3.2wt% of a compatilizer, 1.4-1.8wt% of a lubricant, 0.12-0.15wt% of an antioxidant and 0.06-0.07wt% of a light stabilizer, and the rest is modified polyester resin.

[0008] The modified polyester resin is prepared by the following method:

[0009] Step A1: trifluoroacetate methyl ester, diallylamine and anhydrous tetrahydrofuran are mixed under a dry atmosphere, sodium hydride is slowly added at room temperature, and the reaction is stirred for 3-4h, then the pressure is increased to 4-5bar by using dry nitrogen, the temperature is increased to 55-65 DEG C, and the reaction is continued for 1.5-2h, tetrahydrofuran is removed by rotary evaporation, the substrate is washed with water, the aqueous phase is separated and vacuum dried to obtain an intermediate;

[0010] Further, the amount ratio of trifluoroacetate methyl ester, diallylamine, sodium hydride and anhydrous tetrahydrofuran is 0.1mol:0.102-0.104mol:0.6-0.8g:45-55mL, under the promotion of sodium hydride, trifluoroacetate methyl ester and diallylamine are subjected to amine-ester exchange, and the specific reaction is as follows:

[0011]

[0012] Step A2: the photosensitizer is dissolved in acetone and then added to the intermediate and stirred, ultraviolet irradiation is carried out at 350-400mW / cm 2 mercaptoethanol is slowly added and stirred for 3.8-4.4h, and acetone is removed by rotary evaporation to obtain a modified monomer;

[0013] Further, the amount ratio of the intermediate, mercaptoethanol, photosensitizer and acetone is 0.1mol:0.2mol:30-40mg:65-80mL, under the initiation of ultraviolet, the photosensitizer promotes the click addition reaction of the intermediate and mercaptoethanol, and the specific reaction is as follows:

[0014]

[0015] Step A3: terephthalic acid, ethylene glycol and the modified monomer are premixed, antimony glycol is added, nitrogen is introduced for protection, the temperature is increased to 220-230 DEG C, esterification is carried out for 3-3.5h, then titanium glycol is added, the pressure is reduced to 0.1kPa, the temperature is increased to 270-280 DEG C, polycondensation is carried out for 1.5-2h, the material is discharged and cooled to obtain the modified polyester resin;

[0016] Further, the alcohol acid molar ratio of terephthalic acid, ethylene glycol and modified monomer is 1.4-1.55, the molar ratio of ethylene glycol and modified monomer is 1:0.18-0.26, the amount of ethylene glycol antimony is 50-60ppm, the amount of ethylene glycol titanium is 10-15ppm; the modified monomer and ethylene glycol are copolymerized with terephthalic acid.

[0017] Preferably, the lubricant is a polyester wax, which has good internal and external lubrication effects in the modified polyester resin matrix.

[0018] A preparation method of an anti-pilling wear-resistant composite fabric, comprising the following steps:

[0019] Step S1: mixing nano active alumina, a compatibilizer, a lubricant, an antioxidant, a light stabilizer and a modified polyester resin, extruding and calendering at 260-270 DEG C to form a blank film, and then bidirectionally stretching the blank film to obtain a moisture-permeable polyester film;

[0020] Step S2: sequentially attaching a hot melt adhesive mesh film and the moisture-permeable polyester film to the surface of the base cloth, and hot-pressing to form a composite fabric.

[0021] Further, the stretching ratio of bidirectional stretching is 1.8-2.2, which can maintain good moisture permeability of the film material and good mechanical properties.

[0022] Further, the hot melt adhesive mesh film is a PES mesh film, the hot-pressing temperature is 120-130 DEG C, and the pressure is 0.4-0.5 MPa, so that the polyester material has excellent adhesion and high adhesion stability.

[0023] The present application has the following advantages:

[0024] The application is based on laminated composite technology, and the prepared composite fabric has excellent anti-pilling and wear-resistant performance, while maintaining good moisture permeability and waterproofness; the moisture permeable polyester film of the composite fabric uses a self-developed modified polyester resin as a film forming material, which is prepared from an intermediate prepared by amine-ester exchange of methyl trifluoroacetate and diallylamine, and a modified monomer prepared by click addition of mercaptoethanol and double bonds introduced in the intermediate molecules, and the modified polyester resin is prepared from the modified monomer, ethylene glycol and terephthalic acid copolymerization; compared with the existing PET anti-pilling and wear-resistant fabric protective layer, the modified monomer introduces a thioether-containing tertiary amine structure in the polyester macromolecule by block copolymerization, which forms a chelation effect with nano active alumina, promotes the dispersion of nano active alumina, and makes the pores more uniform; under the chelation effect, the modified monomer chain segment introduces a fluorine structure with low surface energy and low friction on the surface of nano active alumina, which is more easily to form micro pores in the process of biaxial stretching; these uniformly dispersed micro pores greatly increase the moisture permeability of the film, at the same time, the pore size of these micro pores is small, which can effectively hinder the penetration of liquid water, thereby maintaining good moisture permeability and waterproofness; under the chelation effect, the nano active alumina and the modified polyester resin macromolecular chain have interaction force, which still strengthens the film layer, so that the film layer maintains excellent mechanical properties and wear-resistant performance. BRIEF DESCRIPTION OF DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following will briefly introduce the drawings needed to be used in the description of the embodiments. Obviously, the drawings in the following description are only some embodiments of the present application, and for those skilled in the art, other drawings can also be obtained without creative labor.

[0026] Figure 1 The scanning electron microscope image of the moisture permeable polyester film prepared for the embodiment 4 of the present application. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present application will be described clearly and completely in the following with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only some embodiments of the present application, not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the present application.

[0028] Embodiment 1, preparation of anti-pilling and wear-resistant composite fabric, the specific implementation process is as follows:

[0029] (1) Preparation of modified polyester resin

[0030] Step A1: Dry nitrogen gas was introduced into the reactor, and methyl trifluoroacetate, diallylamine, and anhydrous tetrahydrofuran were added and mixed. Sodium hydride was slowly added at room temperature and the mixture was stirred for 4 hours. Then, the pressure was increased to 4 bar with dry nitrogen gas, and the temperature was raised to 55°C and the reaction was continued for 2 hours. The ratio of methyl trifluoroacetate, diallylamine, sodium hydride, and anhydrous tetrahydrofuran was 0.1 mol: 0.102 mol: 0.6 g: 45 mL. After the reaction, tetrahydrofuran was removed by rotary evaporation. The substrate was washed with water, the aqueous phase was separated, and the mixture was dried under vacuum to obtain the intermediate.

[0031] Step A2: Mix the photosensitizer and acetone, then add the intermediate and mix well. Incubate at room temperature at 350 mW / cm². 2 The mixture was subjected to ultraviolet irradiation, and mercaptoethanol was slowly added and stirred for 4.4 h. The photosensitizer used was photosensitizer 651. The ratio of intermediate, mercaptoethanol, photosensitizer and acetone was 0.1 mol: 0.2 mol: 30 mg: 65 mL. After the reaction, the acetone was removed by rotary evaporation to obtain the modified monomer.

[0032] Step A3: Premix terephthalic acid, ethylene glycol, and modified monomers, then add antimony glycolate and mix. Under nitrogen protection, heat to 220℃ for esterification reaction for 3.5h. Then add titanium glycolate, reduce pressure to 0.1kPa, and heat to 270℃ for polycondensation reaction for 2h. The molar ratio of alkyd to acid in the reaction raw materials is 1.4, the molar ratio of ethylene glycol to modified monomer is 1:0.18, the amount of antimony glycolate is 60ppm, and the amount of titanium glycolate is 15ppm. After cooling, the modified polyester resin is obtained.

[0033] (2) Preparation of moisture-permeable polyester face mask

[0034] The raw materials were prepared according to the following composition: 19 wt% nano-activated alumina, using commercially available ALuna-2302 type raw material; 2.5 wt% compatibilizer, using commercially available maleic anhydride-grafted POE type N216; 1.4 wt% lubricant, using CERALENE® 691 type polyester wax; 0.12 wt% antioxidant, using antioxidant 1010 and antioxidant 168 compounded in equal weight ratio; 0.07 wt% light stabilizer, using commercially available light stabilizer 770; the balance was modified polyester resin, prepared in-house according to this embodiment.

[0035] Each component is added to a high-speed mixer and stirred at 600 rpm for 15 minutes. The mixture is then extruded and calendered at 260°C to form a preform. The preform is then biaxially stretched at 130°C with a stretch ratio of 2.2 to obtain a breathable polyester face mask.

[0036] (3) Preparation of composite fabrics

[0037] The hot melt adhesive mesh film (PES mesh film, i.e. polyether sulfone mesh film, is used in the implementation process) and the moisture-permeable polyester surface film are sequentially attached to the surface of the base fabric, and are sent into a hot press, the temperature is controlled to be 120°C, the pressure is 0.4 MPa, the pressure holding time is 55 s, and the composite surface fabric is prepared through hot pressing.

[0038] Example 2, preparation of an anti-pilling wear-resistant composite surface fabric, the specific implementation process is as follows:

[0039] (1) Preparation of modified polyester resin

[0040] Step A1: dry nitrogen is introduced into the reactor, methyl trifluoroacetate, diallylamine and anhydrous tetrahydrofuran are mixed, sodium hydride is slowly added at room temperature, and stirring is performed for 3 h, then dry nitrogen is pressurized to 5 bar, and the temperature is increased to 65°C for continuous reaction for 1.5 h, wherein the amount ratio of methyl trifluoroacetate, diallylamine, sodium hydride and anhydrous tetrahydrofuran is 0.1 mol:0.104 mol:0.8 g:55 mL, after the reaction, tetrahydrofuran is removed by rotary evaporation, the substrate is washed with water, the aqueous phase is separated and vacuum dried to obtain an intermediate.

[0041] Step A2: the photosensitizer and acetone are mixed to dissolve, then the intermediate is added and mixed, ultraviolet irradiation is performed at 400 mW / cm 2 at room temperature, and then mercaptoethanol is slowly added and stirred for 3.8 h, wherein the photosensitizer is photosensitizer 651, and the amount ratio of the intermediate, mercaptoethanol, photosensitizer and acetone is 0.1 mol:0.2 mol:40 mg:80 mL, after the reaction, acetone is removed by rotary evaporation to obtain a modified monomer.

[0042] Step A3: terephthalic acid, ethylene glycol and the modified monomer are pre-mixed, then antimony glycol is added and mixed, nitrogen is introduced for protection, the temperature is increased to 230°C for esterification reaction for 3 h, then titanium glycol is added, the pressure is reduced to 0.1 kPa, and the temperature is increased to 280°C for polycondensation reaction for 1.5 h, wherein the molar ratio of alcohol to acid in the reaction raw materials is 1.55, the molar ratio of ethylene glycol to the modified monomer is 1:0.26, the amount of antimony glycol is 50 ppm, and the amount of titanium glycol is 10 ppm, the discharge is cooled to obtain the modified polyester resin.

[0043] (2) Preparation of moisture-permeable polyester surface film

[0044] According to the component, the raw materials are taken: 27wt% of nano active alumina, ALuna-2302 type commercially available raw material is selected; 3.2wt% of a compatibilizer, N216 type commercially available maleic anhydride grafted POE is selected; 1.8wt% of a lubricant, CERALENE®691 type polyester wax is selected; 0.15wt% of an antioxidant, antioxidants 1010 and 168 are compounded according to equal weight ratio; 0.06wt% of a light stabilizer, commercially available light stabilizer 770 is selected; and the balance is the modified polyester resin, which is self-made in this embodiment.

[0045] The components were added to a high-speed mixer, stirred at 600 rpm for 15 min, and then the mixture was extruded at 270℃ and calendered into a film. The film was biaxially stretched at 130℃ with a stretching ratio of 1.8 to obtain a breathable polyester film.

[0046] (3) Preparation of the composite fabric

[0047] The hot melt adhesive film and the breathable polyester film were sequentially attached to the surface of the base fabric, and then the composite fabric was prepared by hot pressing in a hot press at a temperature of 130℃ and a pressure of 0.5 MPa for 45 s.

[0048] Example 3: Preparation of an anti-pilling and wear-resistant composite fabric, the specific implementation process is as follows:

[0049] (1) Preparation of modified polyester resin

[0050] Step A1: Dry nitrogen was introduced into the reactor, and methyl trifluoroacetate, diallylamine and anhydrous tetrahydrofuran were mixed. Sodium hydride was slowly added at room temperature and stirred for 3.5 h. Then, the pressure was increased to 5 bar with dry nitrogen, and the temperature was increased to 60℃ for continuous reaction for 1.7 h. The amount ratio of methyl trifluoroacetate, diallylamine, sodium hydride and anhydrous tetrahydrofuran was 0.1 mol:0.103 mol:0.7 g:50 mL. After the reaction, tetrahydrofuran was removed by rotary evaporation, the substrate was washed with water, the aqueous phase was separated and vacuum dried to obtain an intermediate.

[0051] Step A2: The photosensitizer and acetone were mixed, and then the intermediate was added and mixed. UV irradiation was performed at 380 mW / cm 2 at room temperature, and then mercaptoethanol was slowly added and stirred for 4.2 h. The amount ratio of photosensitizer, intermediate, mercaptoethanol, photosensitizer and acetone was 0.1 mol:0.2 mol:35 mg:75 mL. After the reaction, acetone was removed by rotary evaporation to obtain a modified monomer.

[0052] Step A3: The terephthalic acid, ethylene glycol and modified monomer were pre-mixed, and then antimony glycol was added and mixed. Nitrogen was introduced for protection, the temperature was increased to 230℃ for esterification reaction for 3.2 h, and then titanium glycol was added. The pressure was reduced to 0.1 kPa, the temperature was increased to 270℃ for polycondensation reaction for 1.6 h. The molar ratio of alcohol to acid in the reaction raw materials was 1.45, the molar ratio of ethylene glycol to modified monomer was 1:0.22, the amount of antimony glycol was 50 ppm, and the amount of titanium glycol was 15 ppm. The material was cooled after discharge to obtain a modified polyester resin.

[0053] (2) Preparation of a breathable polyester film

[0054] The raw materials were taken according to the components: 24wt% of nano active alumina, ALuna-2302 type commercially available raw material was selected; 2.9t% of compatibilizer, N216 type commercially available maleic anhydride grafted POE was selected; 1.6wt% of lubricant, CERALENE®691 type polyester wax was selected; 0.14wt% of antioxidant, antioxidant 1010 and antioxidant 168 were compounded according to equal weight ratio; 0.06wt% of light stabilizer, commercially available light stabilizer 770 was selected; and the balance was modified polyester resin, which was self-made in the example.

[0055] The components were added to a high mixer, stirred at 600rpm for 15min, and then the mixture was extruded and calendered at 260℃ to form a blank film. The blank film was bidirectionally stretched at 130℃, and the stretching ratio was controlled at 1.9 to obtain a moisture permeable polyester film.

[0056] (3) Preparation of composite fabric

[0057] The hot melt adhesive net film and the moisture permeable polyester film were sequentially attached to the surface of the base fabric, and then sent into a hot press, with the temperature controlled at 120℃, the pressure at 0.4MPa, and the holding pressure time at 50s. The hot pressing was performed to prepare a composite fabric.

[0058] Example 4, preparation of anti-pilling and wear-resistant composite fabric, the specific implementation process is as follows:

[0059] (1) Preparation of modified polyester resin

[0060] Step A1: dry nitrogen was introduced into the reactor, methyl trifluoroacetate, diallylamine and anhydrous tetrahydrofuran were added, sodium hydride was slowly added at room temperature, and the mixture was stirred for 4h. Then, the pressure was increased to 4bar with dry nitrogen, and the temperature was increased to 55-℃, and the reaction was continued for 1.8h. The amount ratio of methyl trifluoroacetate, diallylamine, sodium hydride and anhydrous tetrahydrofuran was 0.1mol:0.102mol:0.67g:50mL. After the reaction, tetrahydrofuran was removed by rotary evaporation, the substrate was washed with water, the aqueous phase was separated and vacuum dried to obtain an intermediate.

[0061] Step A2: the photosensitizer and acetone were mixed, then the intermediate was added and mixed, and then the mixture was irradiated with ultraviolet light at 350mW / cm 2 at room temperature, and then mercaptoethanol was slowly added and stirred for 4h. The amount ratio of photosensitizer, intermediate, mercaptoethanol, photosensitizer and acetone was 0.1mol:0.2mol:40mg:70mL. After the reaction, acetone was removed by rotary evaporation to obtain a modified monomer.

[0062] Step A3: premix terephthalic acid, ethylene glycol and modified monomer, then add ethylene glycol antimony mixture, protect by nitrogen, heat to 230°C, esterification reaction for 3.5h, then add titanium glycolate, reduce pressure to 0.1kPa, heat to 280°C, polycondensation reaction for 1.7h, wherein the molar ratio of alcohol to acid in the reaction raw materials is 1.5, the molar ratio of ethylene glycol to modified monomer is 1:0.21, the amount of ethylene glycol antimony is 60ppm, the amount of titanium glycolate is 10ppm, discharge and cool to obtain the modified polyester resin.

[0063] (2) Preparation of the moisture permeable polyester film

[0064] The raw materials were taken according to the components: 22wt% of nano active alumina, ALuna-2302 type commercially available raw material was selected; 2.8wt% of a compatibilizer, N216 type commercially available maleic anhydride grafted POE was selected; 1.6wt% of a lubricant, CERALENE®691 type polyester wax was selected; 0.13wt% of an antioxidant, antioxidant 1010 and antioxidant 168 were compounded according to equal weight ratio; 0.06wt% of a light stabilizer, commercially available light stabilizer 770 was selected; the balance was a modified polyester resin, which was self-made in this example.

[0065] The components were added to a high-speed mixer, stirred at 600rpm for 15min, then the mixture was extruded at 270°C and calendered into a film, the film was bidirectionally stretched at 130°C, the stretching ratio was controlled at 2.0, and a moisture permeable polyester film was obtained.

[0066] (3) Preparation of the composite fabric

[0067] The hot melt adhesive film and the moisture permeable polyester film were sequentially attached to the surface of the base fabric, and were sent into a hot press, the temperature was controlled at 130°C, the pressure was 0.5MPa, and the holding pressure time was 50s, and a composite fabric was prepared by hot pressing.

[0068] In the comparative example 1, the modified polyester resin was replaced by commercially available CB-608 type PET resin raw material, and the rest of the implementation process was exactly the same as that of the example 4.

[0069] In the comparative example 2, 0.35wt% of tridecafluorooctyltrimethoxysilane was additionally added to the comparative example 1, the balance was quantified to 100wt% by CB-608 type PET resin, and the rest of the implementation process was exactly the same as that of the comparative example 1.

[0070] The moisture-permeable polyester face film prepared as above was subjected to relevant performance tests, specifically including: abrasion resistance test according to ASTM D4966-22 standard, load of 12 kPa, abrasive material of standard wool felt, and the number of rubs at surface breakage was recorded; anti-pilling test according to GB / T4802.1-2008 standard, surface pilling grade after 5000 rubs was evaluated; moisture permeability test according to ASTM E96-14 standard, test period of 24 h; water resistance test according to AATCC 127-2018 standard; tensile test according to ASTM D882-18 standard, tensile rate of 50 mm / min; and the specific test results are shown in Table 1:

[0071] Table 1

[0072]

[0073] From the test results in Table 1, it can be seen that the polyester face layer composite fabric has excellent anti-pilling effect, the moisture-permeable polyester face film prepared in the examples has higher abrasion resistance and mechanical strength, while maintaining good moisture permeability and water resistance, and has higher comfort when applied to garment fabric.

[0074] To observe the apparent morphology of the moisture-permeable polyester face film, the moisture-permeable polyester face film prepared in Example 4 was used as a sample, and a German Zeiss EVO10 type scanning electron microscope was used for observation, as shown in Figure 1 .

[0075] From Figure 1 it can be seen that the nano active alumina in the moisture-permeable polyester face film is uniformly dispersed, the nano active alumina and the polyester matrix have a connection area and obvious micro gaps, and no visible tearing cracks are visible.

[0076] In the description of the specification, the description of the reference terms "one embodiment", "example", "specific example" and the like means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are contained in at least one embodiment or example of the present application. In the present specification, the illustrative description of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0077] The above is only an example and description of the concept of the present application, and those skilled in the art can make various modifications or supplements or use similar ways to replace the described specific embodiments, as long as they do not deviate from the concept of the invention or exceed the scope defined by the present claims, which shall fall within the protection scope of the present application.

Claims

1. An anti-pilling wear-resistant composite fabric, which is formed by hot-pressing a base cloth, a hot-melt adhesive screen film and a moisture-permeable polyester surface film, characterized in that, The components of the moisture-permeable polyester film are: 19-27 wt% of nano active alumina, 2.5-3.2 wt% of a compatibilizer, 1.4-1.8 wt% of a lubricant, 0.12-0.15 wt% of an antioxidant, and 0.06-0.07 wt% of a light stabilizer, and the balance is a modified polyester resin; The modified polyester resin is prepared by the following method: Step A1: trifluoroacetic acid methyl ester, diallylamine and anhydrous tetrahydrofuran are mixed under a dry atmosphere, sodium hydride is slowly added to promote amine transesterification, and an intermediate is prepared; Step A2: the photosensitizer and acetone are mixed and then added to the intermediate, and then mercaptoethanol is slowly added under ultraviolet irradiation to perform a click addition reaction, and a modified monomer is prepared; Step A3: terephthalic acid, ethylene glycol and the modified monomer are premixed, then ethylene glycol antimony is added, and esterification is carried out under nitrogen protection at 220-230°C, then titanium glycol is added, and polycondensation is carried out under reduced pressure at 270-280°C, and the modified polyester resin is obtained after discharging and cooling.

2. The anti-pilling wear-resistant composite fabric according to claim 1, characterized in that, The amount ratio of trifluoroacetic acid methyl ester, diallylamine, sodium hydride and anhydrous tetrahydrofuran is 0.1 mol: 0.102-0.104 mol: 0.6-0.8 g: 45-55 mL.

3. The anti-pilling wear-resistant composite fabric according to claim 2, characterized in that, The amount ratio of the intermediate, mercaptoethanol, photosensitizer and acetone is 0.1 mol: 0.2 mol: 30-40 mg: 65-80 mL.

4. The anti-pilling wear-resistant composite fabric according to claim 3, characterized in that, The alcohol acid molar ratio of terephthalic acid, ethylene glycol and the modified monomer is 1.4-1.55, the molar ratio of ethylene glycol and the modified monomer is 1:0.18-0.26, the amount of ethylene glycol antimony is 50-60 ppm, and the amount of titanium glycol is 10-15 ppm.

5. The anti-pilling wear-resistant composite fabric according to claim 1, characterized in that, The lubricant is a polyester wax.

6. A method of making the anti-pilling abrasion resistant composite fabric according to any one of claims 1-5, characterized in that, The method comprises the following steps: Step S1: nano active alumina, a compatibilizer, a lubricant, an antioxidant, a light stabilizer and a modified polyester resin are mixed, extruded and calendered at 260-270°C to form a blank film, and then the blank film is stretched in two directions to obtain a moisture-permeable polyester film; Step S2: a hot melt adhesive mesh film and a moisture-permeable polyester film are sequentially attached to the surface of the base fabric, and hot pressing is performed to obtain a composite fabric.

7. The method for preparing an anti-pilling and abrasion-resistant composite fabric according to claim 6, characterized in that, The stretching ratio of the two-way stretching is 1.8-2.

2.

8. The method for preparing an anti-pilling and abrasion-resistant composite fabric according to claim 6, characterized in that, The hot melt adhesive mesh film is a PES mesh film, and the hot pressing temperature is 120-130°C and the pressure is 0.4-0.5 MPa.

Citation Information

Patent Citations

  • Preparation method of waterproof, moisture-permeable and air-permeable film-coated fabric

    CN116373436A

  • High-wear-resistance composite colored spun yarn and preparation method thereof

    CN118756373A